Radiative transfer in the atmosphere and ocean - Thomas, Gary E. (Cambridge atmospheric and space science series, 1999)
This text provides a foundation in both the theoretical and practical aspects of radiative transfer, for advanced students of atmospheric, oceanic and environmental sciences. The transfer of solar and infrared radiation through optically-thick clouds, aerosol layer, and the oceanic mixed layer is presented through the use of heuristic models of scattering and absorption, and a systematic approach to formulation and solution of the radiative transfer equation. Problems such as the transmission of ultraviolet radiation through the atmosphere and ocean, remote sensing, solar heating and infrared cooling processes, UV biological dose rates, and greenhouse warming are solved using a variety of methods. This self-contained, systematic treatment will prepare students from a range of disciplines in problems concerning the effects of solar and infrared radiation on natural systems. The hardback edition received excellent reviews